Anti-osteoporotic drugs affect the pathogenesis of gut microbiota and its metabolites: a clinical study - Zhang, Rui-kun; Yan, Kun; Chen, Hai-feng; Zhang, Yang; Li, Gui-jin; Chen, Xiao-gang; Ge, Lin-pu; Cheng, Feng; Chen, Zhi-neng; Yao, Xin-miao (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: Disordered gut microbiota (GM) structure and function may contribute to osteoporosis (OP). This study explores how it affects the structure and function of GM in patients with OP through the way of traditional Chinese medicine (TCM) interventions. Method: Through a 3-month clinical study, 43 patients were randomly divided into two groups receiving conventional treatment and combined TCM (Yigu Decoction,YGD) treatment, respectively. The correlation between intestinal flora and its metabolites was analyzed using 16S rDNA and Untargeted metabolism and the combination of the two. Result: After three months of treatment, patients in the treatment group had better bone mineral density (BMD) than those in the control group (P < 0.05). Patients in the treatment group had obvious abundance changes of GM, such as: Bacteroides, Escherichia-Shigella, Faecalibacterium, Megamonas, Blautia, Klebsiella, Romboutsia, Akkermansia, Prevotella_9. Its functional changes mainly focus on: Metabolic function，Genetic information processing and Cellular processes. The metabolites in which major changes occur are: Capsazepine, Phe-Tyr, Dichlorprop, Capsazepine, D-pyroglutamic acid and Tamsulosin. They may act through metabolic pathways, citrate cycle (TCA cycle) and beta alanine metabolism. Joint analysis studies showed that the main acting metabolites were: Dichlorprop, Capsazepine, D-pyroglutamic acid and Tamsulosin Conclusion: This project study showed that TCM intervened on the structure and function of GM in patients with OP, which may be one mechanism of TCM promoting the rehabilitation of patients with OP through GM.